Mitochondrial Stress Links Environmental Triggers with Pro-Inflammatory Signaling in Crohn's Disease - Martín-Reyes, Flores; Bernal, Manuel; Rodríguez-Díaz, Cristina; Rodríguez-de los Reyes, Damaris; Ho-Plagaro, Ailec; Rodríguez-Pacheco, Francisca; Camacho- Martel, Laura; Camargo-Camero, Raquel; Rodríguez-González, Francisco J; Alcaín-Martínez, Guillermo; Martin‐Masot, Rafael; Navas-López, Víctor Manuel; et al. (MDPI, 2023)
Inflammatory Bowel Diseases (IBD) are a group of chronic, inflammatory disorders of the gut. The incidence and activity of IBD are determined by both genetic and environmental factors. Among these factors, polymorphisms in genes related to autophagy and the consumption of non-steroidal anti-inflammatory drugs (NSAIDs) have been consistently associated with IBD. We show that NSAIDs induce mitochondrial stress and mitophagy in intestinal epithelial cells. In an altered mitophagy context simulating that observed in IBD patients, NSAID-induced mitochondrial stress leads to the release of mitochondrial components, which act as Danger Associated Molecular Patterns with pro-inflammatory potential. Furthermore, colonic organoids from Crohn's disease patients and healthy donors show activation of the mitochondrial Unfolded Protein Response (UPRmt) upon treatment with ibuprofen. Finally, colon biopsies from Crohn's disease patients in remission or with low-to-moderate activity also show expression of genes involved in UPRmt, while patients with severe activity show no increase compared to healthy donors. Our results suggest the involvement of mitochondria in the mechanisms triggering inflammation in IBD after NSAID use. Moreover, our results highlight the clinical relevance of mitochondrial stress and activation of the UPRmt pathway in the pathophysiology of Crohn's disease.
Keywords: Mitocondrias; Crohn’s disease; inflammatory bowel diseases; mitochondrial unfolded protein response; non-steroidal anti-inflammatory drugs